Connaissances et pratiques des médecins généralistes sur la prise en charge du diabète sucré dans la ville de Kisangani en RD. Congo. - Valentin, BOLEKALEKA SINGA; Raphael, Musafiri Yanyelo; Charles , Kisolokele liteni; Dieu donné, Mokakando Moyangombe; Ley , Bafeno Liande; Paulin , Ewaya Elide; Jean Pierre, Mokili Kamunyonge (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
Introduction: The diabetes mellitus is a very widespread nontransferable illness in the world. His/her/its increasing prévalence in Africa Subsaharienne requires a hold in adequate charge. Thus, the objective of this work was to value the knowledge and pratices of the general practitioners on the hold in charge of the diabetes mellitus in the city of Kisangani. Material and methods: We achieved a transversal investigation, during the period of 01September 2019 to 31 August 2020, using a questionnaire of investigation structured, auto-managed, on paper, by the general practitioners affected in the five structures of health in the city of Kisangani (DR Congo).  The data colleced were encodée in a Excel workbook then analyzed  using the sort ware Epi  info 7.Results: In the total, 57 general practitioners (GP) was included in this study, among which 77,3% were masculine with in the intermediation age of 39,1± 4,8 years and 59,6% had a professional experience of 5-10 years. Theoreticalty the definition of the diabetes mellitus were badly known (score <30). The initial evaluating of the diabetic patient was not good (score <50).   In relation with their practices on the means of the diabetes treatment, 86%  not referred the diabetic patients to the nutritionists, 57,8% prescribed the Biguanideses as oral antidiabétiques. Apart from this, 73,6% gave the insulin to the diabetic patient, 50,8% had declared that the main indication of the insulin was the infection. By the end, 92,9% programmed the appointments of following-up of diabetic patients, 71,9% among them organized the appointment of following-up once in one month; 56,1% evaluated the adhesion of the diabetic patients to the treatment and 52,6% used the non standardized method of  evaluating the therapeutic adhesion. Conclusion: This study demonstrates that the level of theoretical knowledge of the general practitioners on the mellitus diabetes is relatively low. This is how the organization of theoretical and pratices formation sessions to the profit of the general practitioners proves to be indispensable.